Efficient photocatalytic degradation of Rhodamine B by a novel CeO2/Bi2WO6composite film - Sudarat Issarapanacheewin (2018)
© 2016 Elsevier B.V. The CeO2, Bi2WO6and 0.4CeO2/0.6Bi2WO6photocatalyst films were fabricated by a doctor blading method. The film thickness of the as-prepared samples was varied to one, two and three layers. The physicochemical properties of all sample films were characterization by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), UV–vis spectroscopy, and photoluminescence (PL) techniques. Photocatalytic activities of CeO2, Bi2WO6and 0.4CeO2/0.6Bi2WO6films were investigated via the degradation of Rhodamine B (RhB) under visible light irradiation. The three-layered films of 0.4CeO2/0.6Bi2WO6composite exhibit the highest photocatlytic activity. It was found that the synergistic effect of CeO2and Bi2WO6causes the enhanced photocatalytic activity of 0.4CeO2/0.6Bi2WO6composite by improving efficiency of interfacial charge transfer process. The formation of hydroxyl radicals (OH) on the surface of visible-light illuminated the composite film was detected by the luminescence technique using terephthalic acid as probe molecules. Based on the results of the present study, a reasonable mechanism of photocatalysis on CeO2/Bi2WO6composite under visible light was proposed.